Understanding the drivers of tourists explicit recommendations - Guerreiro, J. (7th International Conference on Tourism Management and Related Issues, 2017)
One of the most challenging decisions of every tourist when arriving at an unknown destination is to choose the places to visit. Recommendation sites such as TripAdvisor or Yelp are crucial to guide tourists on where to find the places that best fit their expectations (Litvin, 2015). One such example is the choice for a restaurant and how to find a place to enjoy a good meal while in a foreign city. While exploring reviews, consumer look for how their peers evaluate a given experience and particularly if they explicitly recommend it to others. Therefore, exploring what drives tourists to write a review with an explicit recommendation may help managers to focus their operational efforts on a better customer satisfaction on such drivers.